Pengaruh Earning Per Share, Debt To Equity Ratio dan Return On Equity Terhadap Harga Saham (Studi Empiris pada Perusahaan Real Estate and Property di BEI Periode Tahun 2012- 2014) - Hapsari Windiastuti, Kartika, Drs. Agus Endro Suwarno, M.Si (2015)
This study aims to determine the effect of earnings per share, debt to quity ratio and return on equity to the stock price on the real estate and property companies on the Stock Exchange in the period from 2012 to 2014. The population used in this study are all the real estate and property company listed on the Indonesia Stock Exchange.Sampling was done by purposive sampling method.The number of samples collected as many as 30 companies with 90 data.With the data, the outliers as much as 40 to 50 samples of data.The collected data were analyzed using data analysis first conducted classical assumption test before hypothesis test.Testing the hypothesis in this study using multiple regression analysis with t-test, f and the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0.350, which means that 35% of the stock price is affected earnings per share, debt to equity ratio and return on equity while the balance of 65% is influenced by other variables outside the research.Hypothesis test results showed that the earnings per share effect on stock prices, while the debt to equity ratio and return on equity has no effect on stock prices. Keywords: earnings per share (EPS), debt to equity ratio (DER), return on equity (ROE), the stock price